The 1st International Electronic Conference on Applied Sciences 2020
DOI: 10.3390/asec2020-07606
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonically-Extracted Marine Polysaccharides as Potential Green Antioxidant Alternatives

Abstract: Marine-extracted sulfated polysaccharides (SPs) have been the subject of myriad research since they are considered an eco-friendly source of biologically active compounds. Meanwhile, food and pharmaceutical industries are urgently producing natural sugar substitutes and antioxidants as alternatives to synthetic ones which are associated with cytotoxicity and safety issues. This study assesses the potential of using marine SPs obtained via the ultrasonic-assisted extraction of different marine species, to utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The carbohydrate content (Figure a) of S. rebaudiana is 75.25% ± 1.24, while that of the green ZnO NPs is 1.04% ± 0.07, which could be owed to the compounds capping the green ZnO NPs . However, the content is significantly lower than that in S.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The carbohydrate content (Figure a) of S. rebaudiana is 75.25% ± 1.24, while that of the green ZnO NPs is 1.04% ± 0.07, which could be owed to the compounds capping the green ZnO NPs . However, the content is significantly lower than that in S.…”
Section: Resultsmentioning
confidence: 90%
“…The FTIR spectrum of the S. rebaudiana extract (Figure b) displays a variety of functional groups, starting with a wide band at 3500–3400 cm –1 , which corresponds to the OH stretch, followed by the sp 3 C–H stretch at 3000–2800 cm –1 . ,, The spectrum also shows bands assigned to the CO stretch of carboxylic acids at 1800–1600 cm –1 , ,, a CC alkene stretch at 1500–1300 cm –1 , , and an ester sulfate band at 1260–1257 cm –1 . The band at 1200–1050 cm –1 could correspond to the C–O stretch of alcohols, ethers, or esters and could be indicative of a glycosidic bond and/or acidic polysaccharides. ,,, The band at 900–800 cm –1 corresponds to the C–H vibration of alkenes and alkynes. , Last, the band at 600–400 cm –1 could be attributed to O–H vibrations in phenols and alcohols or an alkyl halide bond. , The FTIR spectrum of the green ZnO NPs synthesized using the S.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the presence of a band at 1722–1732 cm –1 in the spectrum of H indicates the presence of a CO, which gets weakened in the spectrum of H350 and disappears in the spectrum of H500 consistent with the carbonization and CO 2 release during the activation process. The bands at 1610–1650 cm –1 in the three husks correspond to either the CC alkene stretch or the deformed bending vibrations of the adsorbed water molecules, while the bands at 2300 cm –1 along with the bands at 650 cm –1 in H350 and H500 could be assigned to the adsorbed CO 2 . It can also be observed that the intensity of the CO 2 bands in the spectrum of H350 is higher than their counterparts in the H500 spectrum.…”
Section: Resultsmentioning
confidence: 97%
“…The presence of acidic polysaccharides can also be confirmed by the band shown in the H spectrum at 1053 cm −1 . 22,35 These bands disappeared in H350 and H500 due to the carbonization. Overall, the activated husks exhibit a smaller number of FTIR peaks relative to the unactivated husk since activation involves breaking down and carbonization of the husk material.…”
Section: Characteristics Of the Husksmentioning
confidence: 97%
“…The basic principle of UAE is the use of the strong cavitation, mechanical vibration, and heating effect of ultrasonic waves on the medium under certain conditions to enable the solvent to penetrate into the sample. In recent years, UAE has been applied to enhance the extraction polysaccharides from Dictyophora indusiate [39], green pea pods [40], marine algae [41], okra [42], pumpkin seeds [43], and straw mushroom [44]. The formation and rupture of bubbles by cavitation creates a shockwave to enhance the mass transfer and generate energy for β elimination reaction, thereby providing a beneficial effect on the release of ChS into the solution.…”
Section: Comparison Of Conventional Shaking Extraction and Ultrasonic-assisted Extractionmentioning
confidence: 99%